The psychological function in Risk Prevention and Protection Service: perform regulatory requirements or develop organizational competence? - Sarubbo, Maria (Rivista di Psicologia Clinica, 2013)
Among professional workers dealing with health and safety at work; psychologists may address two different approaches in the field of psychosocial risk assessment and intervention. The first one is consistent with an individualistic paradigm of psychology because it uses technique to assess and detect individual problems; the second one considers assessment as a consulting intervention which aims to develop the organizational competence of context based on a relational analysis of events. An ongoing psychological intervention in a hospital in Rome is reported in order to promote this second approach and thus the concept of psychosocial risk according to which intervention deals with relationships not just individuals. The critical events at work are analyzed based on the relationship between individuals and context.